Peripheral Nerve Stimulation for the Treatment of Phantom Limb Pain: A Case Series - Robert Pagan-Rosado; Brandon J. Smith; Fantley C. Smither; Matthew J. Pingree; Ryan S. D’Souza (Case Reports in Anesthesiology, 2023)
This case series aims to highlight the efficacy of peripheral nerve stimulation (PNS) in the treatment of phantom limb pain, as well as provide an alternative method for the treatment of this pain syndrome. In this report, we describe three amputee patients with severe phantom limb pain who obtained substantial analgesia and improvement in physical functionality after implantation of a temporary PNS device. Future studies should assess predictors of successful response or poor response to PNS therapy, such as mental health, environmental stressors, coping skills, and procedural factors. These factors may facilitate an individualized approach for each patient to ensure appropriate candidacy for PNS and better prognosis. Considering that patients in our cohort did not achieve long-lasting benefit after removal of temporary PNS, future research should assess if patients with phantom limb pain would benefit from permanent PNS, rather than temporary PNS.